Lesson Learn David Johnston's Strategic Leadership in Support of Canada's Maritime Security - Putri, Cintya Yelena; Soemantri, Asep Iwa; Prakoso, Lukman Yudho; Suwarno, Panji; Pulungan, Ahmad Ari Syahputra; Alriandi, Aldy Surya; Inayah, Atikah; Faradilla, Auriga Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article examines key lessons learned from David Johnston’s leadership in Canada’s maritime sector. By analyzing the policies and strategies implemented by David Johnston during his tenure, the study identifies effective approaches to enhancing interagency collaboration, human resource development, and the adoption of advanced technologies. Findings show that Johnston’s leadership focused on innovation and operational efficiency, which contributed significantly to the advancement of the maritime sector. The lessons learned from Johnston’s experience can provide valuable guidance for future maritime leaders to address challenges and capitalize on opportunities in a global context.